STABILISASI TANAH LEMPUNG MENGGUNAKAN SEMEN DAN ASPAL EMULSI TERHADAP SUBGRADE PERKERASAN JALAN - Muhammad Ernadi Ramadhan; Suryo Hapsoro Tri Utomo; Latif Budi Suparma (TEKNISIA, 2020)
Several causes can cause pavement deterioration; a weak subgrade caused one of them. If the pavement construction was built on the weak subgrade, it could damage pavement construction at the top of the subgrade. Chemical soil stabilization with cement and bitumen emulsion is one of the solutions to improve soil bearing capacity for pavement subgrade construction. The purpose of this study was to analyze the potential use of cement and bitumen emulsion as materials of chemical soil stabilization for pavement subgrade construction. In this study, soil samples were mixed by cement (3%, 6%,9%) and bitumen emulsion (3%,6%) and cured for 0, 3, and 7 days. The mixture of soil, cement, and bitumen emulsion was tested for soil bearing capacity and soil swelling by CBR and soil swelling test based on ASTM D 1883-99. Preliminary test results concluded that the original soil is included in class A-7-5 at the AASHTO classification system, and it is dominated by smectite clay minerals so that the original soil is expansive clay soil. The results of the compaction test reveal that soil stabilization with cement and bitumen emulsion can increase the mass of dry density of the soil. They reduce the optimum moisture content, where the variation of 6% cement and 3% bitumen emulsion can increase the mass of dry density by 1,340 gr / cm3 and reduce the optimum moisture content of 25%. The CBR and swelling test also disclose that soil stabilization with cement and bitumen emulsion increases soil bearing capacity and reduce swelling. The highest CBR values (soaked and unsoaked) are found in the variation of 9% cement and 3% bitumen emulsion cured by seven days, where the value is 56.9% (CBR Soaked) and 44.01% (CBR Unsoaked). The variation of 9% cement and 3% bitumen emulsion also can reduce soil swelling, where the value is 0,13%. CBR values at the variety of 9% cement and 3% bitumen emulsion cured by seven days have met the requirements of the road pavement subgrade based on SNI 03-1744-1989. Based on these tests, the cement and bitumen emulsion can use for soil stabilization material for subgrade pavement construction.